Konsistensi Tinjaun Pasal 82 Undang-Undang Nomor 6 Tahun 2014 Tentang Chek And Balance Perspektif Siyasah Dusturiyah (Studi Kasus Pada Nagari Situmbuk, Kecamatan Salimpaung, Kabupaten Tanah Datar) - Rahmat Afandi; Dian Pertiwi (UIN Mahmud Yunus Batusangkar, 2023)
This study examines the Review of Article 82 of Law Number 6 of 2014 concerning Check and Balance from the Siyasah Dusturiyah Perspective (Case Study in Nagari Situmbuk, Salimpaung District, Tanah Datar District). The problems are (1) To find out and explain that the Situmbuk┬áNagari Government has carried out functions and supervision (check and balance) based on Article 82 of Law Number 6 of 2014. (2) To find out and explain Siyasa Dusturiyah's views on the implementation of Article 82 of Law Number 6 of 2014 by the Nagari Situmbuk Government. From these problems the question arises (1) Has the Nagari Situmbuk Government carried out its functions and controls (check and balance) based on Article 82 of Law Number 6 of 2014. (2) What is Siyasah Dusturiyah's view of the implementation of Article 82 of Law Number 6 of 2014 by the Nagari Situmbuk Government. This research is a field research. Data was obtained through interviews with Wali Nagari, Jorong Heads, and community leaders. After the data is collected and processed by collecting data and analyzed by examining the data obtained from related information and literature. Collecting data sources, classifying data and compiling data based on categories in research. Interpretation of the data, namely after the data has been collected and classified, then describes the data in appropriate words. After the data is arranged and classified, then draw conclusions to get conclusions to answer the problems that have been examined. This research found that the results of the Situmbuk Nagari Government had not fully carried out its functions and supervision (check and balance) in accordance with what was mandated in Article 82 of Law Number 6 of 2014, based on the results of interviews and research conducted by the author, there were differences in perception between the Wali Nagari and Community leaders in this case were represented by Ninik Mamak, Cadiak Pandai, Alim Ulama, Bundo Kanduang.